Storytelling, Identity Development, and Decolonial Pedagogies: Frameworks for Teaching Indigenous Literatures of the Great Lakes to Young Adult Readers - (:unkn) unknown (My University, 2022)
This project examines Dakota and Anishinaabe literatures of the Great Lakes region with an emphasis on themes of homeland, identity development, community, violence, transformation, and healing. Each chapter of the dissertation focuses on a specific genre, medium, or theory, such as nineteenth-century autobiography, young adult literature, comics, and Two-Spirit critiques, along with pedagogical practices that can be incorporated into English curriculums to help educators teach Indigenous literatures more effectively. This dissertation provides teaching frameworks and suggestions for activities and discussions that other educators can adapt and model in their own secondary school or university classes. I consider texts by Zitkala-Sa, Jane Johnston Schoolcraft, Angeline Boulley, Elizabeth LaPensée, and Joshua Whitehead to model close readings through the lenses of New Historicism, decolonialism, and queer theory. The work of this project seeks to help educators engage with Indigenous methodologies and student-centered pedagogies, thoughtfully reflect on and research tribally specific histories, cultures, and contemporary issues, and choose Indigenous texts focusing on themes that resonate with young adults and which can be read in a way that helps students develop their identities. The chapters of this dissertation work together to argue for a greater inclusion of Indigenous literatures within English courses and other disciplines.